Polar group grafted aramid-based resin as well as preparation method and application thereof

By grafting polar groups onto the aramid resin, the problem of poor circulation stability of the negative electrode material of sodium ion battery is solved, and efficient processing of the material and excellent electrochemical properties are achieved.

CN119798651APending Publication Date: 2025-04-11ZHONGKE DEEP BLUE HUIZE NEW ENERGY (QINGDAO) CO LTD

Patent Information

Application Number
CN202411971656.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing sodium ion battery negative electrode materials face problems such as dendrite generation, side reaction occurrence and sodium ion insertion/exit, resulting in poor circulation stability.

Method used

By grafting polar groups onto the aramid resin, the intermolecular interaction is broken, the material solubility and ionic conductivity are improved, and it is used as an interface modification layer of the electrode material to prevent the electrolyte from contacting the electrode directly and inhibit side reactions.

Benefits of technology

It improves the cycle stability and Coulomb efficiency of the battery, enhances the mechanical properties and ion transport capabilities of the material, and reduces the risk of dendrites and irreversible capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798651A_ABST
    Figure CN119798651A_ABST
Patent Text Reader

Abstract

The invention provides polar group grafted aramid-based resin as well as a preparation method and application thereof, and relates to the technical field of secondary batteries. The polar group grafted aramid-based resin is at least one polar group grafted aramid polymer, and the polar group is selected from one of an ether bond group, a sulfonate group, a quaternary ammonium salt group, a carbonate group, a phosphate group, a sulfimide group and a corresponding derivative group. The polar group grafted aramid-based resin breaks the interaction among aramid resin molecules, improves the solubility of the material, and promotes the modified aramid material to be easy to process and prepare. Meanwhile, the existence of polar groups promotes the interaction between the polymer and ionic groups, so that the ionic conductivity of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a polar group grafted aramid-based resin, a preparation method of the polar group grafted aramid-based resin, a polar group grafted aramid-based resin interface modification layer and a secondary battery. Background Art

[0002] The lack of excellent negative electrode materials has seriously affected the practical application and promotion of sodium-ion batteries. Traditional negative electrode materials face serious problems such as easy formation of dendrites, side reactions, and difficulty in achieving stable sodium ion insertion / extraction. Excellent electrode and electrolyte interface is the key to stabilizing negative electrode materials and preparing long-life secondary batteries.

[0003] A solid electrolyte interface layer (SEI) is formed on the surface of the battery negative electrode material during the electrochemical cycle, and its structure is affected by the electrolyte composition and preparation process. However, the SEI layer formed in situ on the commonly used hard carbon negative electrode of the sodium battery is uneven and has poor structural stability. Invention patent CN202310778519.1 discloses a method of using NASICON or Beta-alumina structure to coat hard carbon materials as a stable artificial SEI layer, which can avoid direct contact between the electrode and the electrolyte and reduce the occurrence of side reactions. At the same time, such materials themselves have excellent sodium ion transport performance to ensure the smooth progress of the electrochemical process in the battery. However, the rigidity of this SEI itself is too strong, which will reduce the cycle stability of the battery. Invention patent CN202111289860.8 discloses a perfluoromethyl vinyl ether / maleic anhydride / 2-vinyl-1H-benzimidazole copolymer as a silicon-carbon negative electrode interface modification layer. Because this polymer has excellent ion transport ability, it reduces the risk of dendrite formation and irreversible capacity of the electrode, effectively improves the cycle stability of the battery, and verifies the feasibility of polymer materials as SEI layers. Invention patent CN101356665A coats aramid material at the interface between the diaphragm and the electrode to achieve simultaneous improvement of battery thermal stability and cycle performance. However, the above aramid material faces problems such as high processing difficulty and low ion conductivity, and the modification and preparation technology of aramid material needs further exploration. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a polar group grafted aramid resin, which grafts polar groups onto aramid resin, breaks the interaction between aramid resin molecules, improves the solubility of the material, and makes the modified aramid material easy to process and prepare. At the same time, the presence of polar groups promotes the interaction between polymers and ionic groups, and improves the ionic conductivity of the material. The amide bonds in the aramid resin are very easy to interact with polar groups or alkali metals, thereby improving the stability of the aramid resin as an interface modification layer of the electrode material.

[0005] The first aspect of the present invention provides a polar group grafted aramid-based resin, wherein the polar group grafted aramid-based resin is an aramid polymer grafted with at least one polar group, and the structure of the polar group grafted aramid polymer is shown in Formula 1 or Formula 2:

[0006]

[0007] Among them, R1 and R2 are both polar group side chains; R1 and R2 are both selected from one of ether bond groups, sulfonate groups, quaternary ammonium salt groups, carbonate groups, phosphate groups, sulfonimide groups and corresponding derivative groups.

[0008] Optionally, the structures of R1 and R2 are as shown in Formula 3,

[0009] *-R3-R4 formula 3;

[0010] Wherein, R3 is selected from any derivative group of an aliphatic group, an aromatic group or a combination thereof; and R4 is selected from any one of an ether group, a sulfonate, a quaternary ammonium salt, a carbonate, a sulfonimide salt or a phosphate.

[0011] Optionally, n is selected from an integer of 10-10000, optionally, n is selected from an integer of 100-10000.

[0012] Optionally, the aliphatic group is a straight-chain or branched aliphatic hydrocarbon group or a fluorine-containing or silicon-containing derivative group thereof; further, the aliphatic group contains an alkane group with a carbon number of 0-20.

[0013] Optionally, the aromatic group is a monocyclic aromatic group, a polycyclic aromatic group or a condensed aromatic group which is unsubstituted or substituted with at least one substituent, wherein the substituent when substituted is one or more of halogen, nitro, hydroxyl or silicon-containing group.

[0014] Optionally, the ether group is an ether-containing group which is unsubstituted or substituted with at least one substituent.

[0015] Alternatively, the sulfonate is a sulfate group whose counter ion is a proton or a metal ion.

[0016] Optionally, the quaternary ammonium salt is a quaternary ammonium salt group whose counter ion is a halide ion, carboxylate, hexafluorophosphate, difluorooxalatoborate, tetrafluoroborate, trifluoromethylsulfonate, bis(fluorosulfonyl imide) and bis(trifluoromethylsulfonyl imide).

[0017] Optionally, the carbonate is an unsubstituted or substituted carbonate group with at least one substituent.

[0018] and / or the sulfonimide salt is a sulfonimide group whose counter ion is a proton or a metal ion.

[0019] Optionally, the phosphate is a phosphate group whose counter ion is a proton or a metal ion.

[0020] Wherein, the substituent is a halogen, a nitro group, a hydroxyl group or a silicon-containing group.

[0021] Optionally, the polar group grafted aramid resin structure may be the following structure:

[0022]

[0023] Wherein, M is selected from metal ions or protons, and X is selected from halide ions, carboxylates, hexafluorophosphates, difluorooxalatoborate, tetrafluoroborate, trifluoromethylsulfonate, bis(fluorosulfonyl imide) or bis(trifluoromethylsulfonyl imide).

[0024] The second aspect of the present invention provides a method for preparing a polar group grafted aramid-based resin, the preparation method comprising the following steps:

[0025] S1: dissolving aramid in a solution of a polar solvent and a solubilizing salt, adding a certain amount of an acid-binding agent and a halogenated polar group monomer, and stirring at a certain temperature to obtain a mixture;

[0026] S2: pouring the mixture obtained in step S1 into a precipitant, and then washing, purifying and drying in sequence to obtain a polar group-grafted aramid-based resin.

[0027] Optionally, in step S1, the mass fraction of the solubilizing salt is 0.1%-20%, the mass fraction of the aramid fiber is 0.1%-30%, the mass fraction of the acid binding agent is 0.1%-20%, and the mass fraction of the halogenated polar group monomer is 1%-20%.

[0028] Preferably, in step S1, the mass fraction of the solubilizing salt is 0.1%-5%, the mass fraction of the aramid is 1%-20%, the mass fraction of the acid-binding agent is 5%-15%, and the mass fraction of the halogenated polar group monomer is 1%-20%. In the preparation process, too little raw material will make it difficult to prepare the polar group-grafted aramid-based resin, and too much will lead to a waste of raw materials and increase costs.

[0029] Optionally, the aramid is selected from one or both of meta-aramid and para-aramid;

[0030] Optionally, the polar solvent is selected from one or more of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, methanol, acetone or ethanol; preferably, the polar solvent is one or more of dimethylacetamide, dimethyl sulfoxide or dimethylformamide.

[0031] Optionally, the dissolving salt is selected from one or more of lithium bromide, potassium bromide, zinc chloride, potassium hydroxide, sodium hydroxide, lithium chloride, calcium chloride, sodium hydride or magnesium chloride; preferably, the dissolving salt is one or both of lithium chloride and sodium hydride.

[0032] Optionally, the acid binding agent is selected from one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide, sodium hydride, cesium carbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate or triethylamine; preferably, the acid binding agent is one or more of potassium hydroxide, sodium hydroxide or potassium carbonate.

[0033] Optionally, the precipitant is selected from one or more of water, methanol, ethanol, hydrochloric acid, sulfuric acid, sodium chloride or sodium carbonate solution. The amount of the precipitant used is 5-20 times the volume of the reaction solution; the preferred amount of the precipitant is 5-10 times.

[0034] Optionally, the halogenated polar group monomer is selected from 2-(2-ethoxyethoxy)ethyl bromide, diethylene glycol-2-bromoethyl methyl ether, 1-bromo-3,6,9,12-tetraoxatridecane, potassium iodooctafluoroethyl ether sulfonate or 4-bromobutyltrimethylammonium bromide.

[0035] Optionally, the certain temperature in step S1 is 0-120° C., preferably 25-80° C. Too high or too low a temperature will increase the difficulty of the operation, making the reaction rate too fast or difficult to proceed, and failing to obtain the target product.

[0036] The third aspect of the present invention provides a polar group grafted aramid resin interface modification layer, wherein the polar group grafted aramid resin interface modification layer comprises the polar group grafted aramid-based resin.

[0037] The preparation method of the polar group grafted aramid resin interface modification layer can be to dissolve the polar group grafted aramid resin in a polar solvent, apply the solution on the electrode surface, and form the interface modification layer after drying.

[0038] Optionally, the polar solvent is selected from one or more of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; preferably, the polar solvent is dimethyl sulfoxide or N-methylpyrrolidone.

[0039] A fourth aspect of the present invention provides a secondary battery, comprising the above-mentioned polar group-grafted aramid resin interface modification layer.

[0040] Compared with the prior art, the present invention achieves at least one of the following beneficial effects:

[0041] (1) The polar groups grafted onto the aramid resin of the present invention break the interaction between the aramid resin molecules, improve the solubility of the material, and facilitate the processing and preparation of the modified aramid material. At the same time, the presence of the polar groups promotes the interaction between the polymer and the ionic groups, thereby improving the ionic conductivity of the material.

[0042] (2) The polar group grafted aramid-based resin of the present invention has good mechanical properties and can improve the cycle stability of the battery.

[0043] (3) The polar group grafted aramid resin interface modification layer of the present invention coats the polar group grafted aramid-based resin on the surface of the electrode material, which can prevent direct contact between the electrolyte and the electrode while ensuring ion transmission, inhibit the occurrence of side reactions, and improve the cycle stability and coulombic efficiency of the electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0045] Figure 1 The polar group grafted aramid-based resin A of the present invention is shown 1 H NMR spectrum;

[0046] Figure 2 The polar group grafted aramid-based resin B of the present invention is shown 1 H NMR spectrum;

[0047] Figure 3 The polar group grafted aramid-based resin C of the present invention is shown 1 H NMR spectrum;

[0048] Figure 4 The polar group grafted aramid-based resin D of the present invention is shown 9 F NMR spectrum;

[0049] Figure 5 The polar group grafted aramid-based resin E of the present invention is shown 1 H NMR spectrum;

[0050] Figure 6 The polar group grafted aramid-based resin F of the present invention is shown 1 H NMR spectrum;

[0051] Figure 7 The mechanical properties diagram of the polar group grafted aramid-based resin A of the present invention is shown;

[0052] Figure 8 The mechanical properties diagram of the polar group grafted aramid-based resin B of the present invention is shown;

[0053] Fig. 9 The mechanical properties diagram of the polar group grafted aramid-based resin C of the present invention is shown;

[0054] Fig.10 The mechanical properties diagram of the polar group grafted aramid-based resin D of the present invention is shown;

[0055] Fig.11 The mechanical properties diagram of the polar group grafted aramid-based resin E of the present invention is shown;

[0056] Fig.12 The mechanical properties diagram of the polar group grafted aramid-based resin F of the present invention is shown;

[0057] Fig.13 The sodium metal electrode coated with the interface modification layer of polar group grafted aramid product A was charged at 30℃ and 0.1mA / cm 2 The constant current polarization curve of

[0058] Fig.14 The sodium metal electrode coated with the interface modification layer of polar group grafted aramid product B was charged at 30℃ and 0.1mA / cm 2 The constant current polarization curve of

[0059] Fig.15 The sodium metal electrode coated with the polar group grafted aramid product C interface modification layer was subjected to 30℃ and 0.1mA / cm 2 The constant current polarization curve of

[0060] Fig.16 The sodium metal electrode coated with the interface modification layer of polar group grafted aramid product D was charged at 30℃ and 0.1mA / cm 2 The constant current polarization curve of

[0061] Fig.17 The sodium metal electrode coated with the interface modification layer of polar group grafted aramid product E was subjected to the conditions of 30℃ and 0.1mA / cm 2 The constant current polarization curve of

[0062] Fig.18 The sodium metal electrode coated with the interface modification layer of polar group grafted aramid product F was subjected to the conditions of 30℃ and 0.1mA / cm 2 The constant current polarization curve of

[0063] Fig.19 The sodium metal electrode without interface modification layer was subjected to 30℃ and 0.1mA / cm 2 The constant current polarization curve of

[0064] Fig. 20SEM characterization of the sodium metal electrode coated with the polar group grafted aramid A interface modification layer;

[0065] Fig.21 This is a SEM characterization of the surface of the sodium metal electrode coated with a polar group-grafted aramid fiber A interface modification layer after 500 cycles;

[0066] Fig. 22 ATR-FTIR infrared images of polar group grafted aramid resin A and resin A coated on the surface of sodium metal. DETAILED DESCRIPTION

[0067] In order to more clearly illustrate the overall concept of the present invention, a detailed description is given below in an exemplary manner in conjunction with the accompanying drawings.

[0068] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0069] Example 1

[0070] Preparation and purification of polar group grafted aramid resin

[0071] Polar group grafted aramid resin A

[0072] The preparation method of polar group grafted aramid-based resin A comprises the following steps:

[0073] S1: 1 g of meta-aramid was dissolved in 10 ml of a solution of polar solvent dimethylacetamide and lithium chloride, 0.5 g of an acid binding agent NaOH, K2CO3 and 1.00 g of 2-(2-ethoxyethoxy)ethyl bromide were added, and the mixture was stirred at 60° C. to obtain a mixture;

[0074] S2: After a period of reaction, the reaction system is precipitated in 100 ml of water, and then washed, purified and dried in sequence to obtain a polar group grafted aramid-based resin, wherein the n value is 200-300 and the structure is shown in Formula A.

[0075] Polar group grafted aramid resin B

[0076] The preparation method of polar group grafted aramid-based resin B comprises the following steps:

[0077] S1: 1 g of meta-aramid was dissolved in 10 ml of a solution of polar solvent dimethylacetamide and lithium chloride, 0.5 g of an acid binding agent NaOH, K2CO3 and 1.20 g of diethylene glycol-2-bromoethyl methyl ether were added, and the mixture was stirred at 50° C. to obtain a mixture;

[0078] S2: After a period of reaction, the reaction system is precipitated in 100 ml of methanol, and then washed, purified and dried to obtain a polar group grafted aramid-based resin with an n value of 200-400 and a structure as shown in Formula B.

[0079] Polar group grafted aramid resin C

[0080] The preparation method of polar group grafted aramid-based resin C comprises the following steps:

[0081] S1: 1 g of meta-aramid fiber was dissolved in 10 ml of a solution of polar solvent dimethylformamide and lithium chloride, 0.5 g of an acid binding agent NaOH, K2CO3 and 1.50 g of sodium 2-bromoethane phosphate were added, and the mixture was stirred at 60° C. to obtain a mixture;

[0082] S2: After a period of reaction, the reaction system is precipitated in 100 ml of ethanol, and then washed, purified and dried to obtain a polar group grafted aramid-based resin with an n value of 300-500 and a structure as shown in Formula C.

[0083] Polar group grafted aramid resin D

[0084] The preparation method of polar group grafted aramid-based resin D comprises the following steps:

[0085] S1: 1 g of meta-aramid fiber was dissolved in 10 ml of a solution of polar solvent dimethyl sulfoxide and sodium hydride, 0.1 g of an acid binding agent NaOH, K2CO3 and 2.00 g of potassium iodooctafluoroethyl ether sulfonate were added, and the mixture was stirred at 60° C. to obtain a mixture;

[0086] S2: After a period of reaction, the reaction system is precipitated in 100 ml of methanol, and then washed, purified and dried to obtain a polar group grafted aramid-based resin with an n value of 300-400 and a structure as shown in Formula D.

[0087] Polar group grafted aramid resin E

[0088] The preparation method of polar group grafted aramid-based resin E comprises the following steps:

[0089] S1: 1 g of meta-aramid fiber was dissolved in 10 ml of a solution of polar solvent dimethyl sulfoxide and sodium hydride, 0.75 g of an acid binding agent NaOH and 2.00 g of 4-bromobutyltrimethylammonium bromide were added, and the mixture was stirred at 40° C. to obtain a mixture;

[0090] S2: After a period of reaction, the reaction system is precipitated in 100 ml of hydrochloric acid, and then washed, purified and dried in sequence to obtain a polar group grafted aramid-based resin with an n value of 200-300 and a structure shown in Formula E.

[0091] Polar group grafted aramid resin F

[0092] The preparation method of polar group grafted aramid-based resin F comprises the following steps:

[0093] S1: 1 g of meta-aramid fiber was dissolved in 10 ml of a solution of polar solvent dimethyl sulfoxide and sodium hydride, 0.80 g of an acid binding agent NaOH and 0.30 g of chloromethyl isopropyl carbonate were added, and the mixture was stirred at 60° C. to obtain a mixture;

[0094] S2: After a period of reaction, the reaction system is precipitated in 100 ml of methanol, and then washed, purified and dried to obtain a polar group grafted aramid-based resin with an n value of 200-400 and a structure shown in Formula F.

[0095] Polar group grafted aramid resin B

[0096] On the basis of polar group grafted aramid resin A, the main difference is that the grafted ether group is longer, which can further increase the distance between aramid molecules, weaken the intermolecular force, and improve the processing performance of aramid.

[0097] Polar group grafted aramid resin C

[0098] Based on the polar group grafted aramid-based resin A, the main difference is that the grafted side chain is a phosphate group.

[0099] Polar group grafted aramid resin D

[0100] Based on the polar group grafted aramid-based resin A, the main difference is that the grafted side chain is a fluorosulfonic acid group.

[0101] Polar group grafted aramid resin E

[0102] Based on the polar group grafted aramid-based resin A, the main difference is that the grafted side chain is a quaternary ammonium salt side chain.

[0103] Polar group grafted aramid resin F

[0104] Based on the polar group grafted aramid-based resin A, the main difference is that the grafted side chain is a carbonate side chain.

[0105] Aramid resin D1

[0106] The main difference between directly using polar groups to graft the meta-aramid in the aramid-based resin A and using polar groups to graft the aramid-based resin is that the meta-aramid resin has no side chain groups.

[0107] Performance Testing

[0108] ①Solubility test

[0109] The polar group-grafted aramid-based resin and aramid resin D1 prepared above were tested for solubility properties, as shown in Table 1.

[0110] Solubility test: Take 0.10g of the above resin and mix it with 9.90g of the selected solvent. After a certain period of time, observe whether a homogeneous solution is formed.

[0111] Table 1

[0112]

[0113] √: dissolved, ×: not dissolved

[0114] As shown in Table 1, compared with the aramid resin D1 raw material, the polar group grafted aramid-based resin prepared in the present application has better solubility and processing performance without solubilizing salt.

[0115] ②NMR characterization

[0116] refer to Figure 1-Figure 6 As shown, Figure 1 The polar group grafted aramid resin A is shown 1 From the H NMR spectrum, it can be seen that the absorption peaks at chemical shifts δ4.0~3.0 and 1.0 correspond to the hydrogen atoms on the ether side chain, proving that the polar group-grafted aramid-based resin was successfully synthesized.

[0117] Figure 2 The polar group grafted aramid resin B 1 From the H NMR spectrum, it can be seen that the absorption peak at the chemical shift of δ4.2~3.0 corresponds to the hydrogen atoms on the ether side chain, proving that the polar group-grafted aramid-based resin was successfully synthesized.

[0118] Figure 3 The polar group grafted aramid resin C 1 From the H NMR spectrum, it can be seen that the absorption peak at the chemical shift of δ4.1-3.0 corresponds to the hydrogen atoms on the side chain of the alkyl phospholipid group, proving that the polar group-grafted aramid-based resin was successfully synthesized.

[0119] Figure 4 The polar group grafted aramid resin D 9 From the F NMR spectrum, it can be seen that the absorption peak at the chemical shift of δ-80 to -140 corresponds to the fluorine atom on the side chain of the perfluoroether fluorosulfonic acid group, proving that the polar group-grafted aramid-based resin was successfully synthesized.

[0120] Figure 5 The polar group grafted aramid resin E 1From the H NMR spectrum, it can be seen that the absorption peak at the chemical shift of δ4.0-3.0 corresponds to the hydrogen atoms on the side chain of the alkyl quaternary ammonium salt, proving that the polar group-grafted aramid-based resin was successfully synthesized.

[0121] Figure 6 The polar group grafted aramid resin F 1 From the H NMR spectrum, it can be seen that the absorption peaks at chemical shifts δ5.5~4.5 and 3.5~3.0 correspond to the hydrogen atoms on the carbonate side chain, proving that the polar group-grafted aramid-based resin was successfully synthesized.

[0122] ③ Mechanical properties test

[0123] The polar group grafted aramid resin prepared above was subjected to mechanical property test. However, since aramid resin D1 needs dissolution-promoting salt to promote dissolution, it is difficult to remove the residual dissolution-promoting salt inside after being made into relevant mechanical property test specimens. Therefore, its mechanical property test data cannot reflect the actual performance of the material. Figure 7-12 And as shown in Table 2.

[0124] Mechanical properties test: The above aramid-based resin is prepared into a casting solution and cast into a film. The obtained film is cut into rectangular specimens and the mechanical properties test is carried out on a universal tensile machine.

[0125] Table 2

[0126]

[0127] Figure 7 The mechanical properties diagram of polar group grafted aramid-based resin A shows that the elongation at break of polar group grafted aramid-based resin A is 5.8% and the breaking strength is 28 MPa, which proves that polar group grafted aramid-based resin A has good film-forming ability and mechanical properties.

[0128] Figure 8 The mechanical properties diagram of polar group grafted aramid-based resin B shows that the elongation at break of polar group grafted aramid-based resin B is 5.0% and the breaking strength is 41 MPa, which proves that polar group grafted aramid-based resin B has good film-forming properties and mechanical properties.

[0129] Fig. 9 The mechanical properties diagram of polar group grafted aramid-based resin C shows that the elongation at break of polar group grafted aramid-based resin B is 5.0% and the breaking strength is 29 MPa, which proves that polar group grafted aramid-based resin C has good film-forming properties and mechanical properties.

[0130] Fig.10The mechanical properties diagram of polar group grafted aramid-based resin D shows that the elongation at break of polar group grafted aramid-based resin D is 5.3% and the breaking strength is 46 MPa, which proves that polar group grafted aramid-based resin D has good film-forming properties and mechanical properties.

[0131] Fig.11 The mechanical properties diagram of polar group grafted aramid-based resin E shows that the elongation at break of polar group grafted aramid-based resin E is 12.4% and the breaking strength is 13 MPa, which proves that polar group grafted aramid-based resin E has good film-forming properties and mechanical properties.

[0132] Fig.12 The mechanical properties diagram of the polar group grafted aramid-based resin F shows that the elongation at break of the polar group grafted aramid-based resin F is 9.3% and the breaking strength is 19 MPa, which proves that the polar group grafted aramid-based resin F has good film-forming properties and mechanical properties.

[0133] Refer to Table 2 and Figure 7-12 As shown, the polar group grafted aramid-based resin prepared in the present application has good film-forming properties and mechanical properties, with an elongation at break of not less than 5.0% and a breaking strength of not less than 13 MPa, which further ensures the subsequent cycle stability of the battery.

[0134] ④Ionic conductivity test

[0135] The polar group grafted aramid-based resin and aramid resin D1 prepared in Example 1 were prepared into solutions, respectively, and then coated or cast and dried to form membrane materials. The membrane material was immersed in an EC / DEC (ethylene carbonate / diethyl carbonate) electrolyte containing 1M NaPF6 to prepare an electrolyte, and was sandwiched between two stainless steel electrodes to measure its AC impedance spectrum, wherein the AC perturbation amplitude was 10mV and the frequency was 7Hz to 100MHz.

[0136] Table 3

[0137]

[0138]

[0139] As shown in Table 3, the polar group-grafted aramid-based resin prepared in the present application has an ionic conductivity that is better than that of the unmodified aramid material.

[0140] ⑤Electrochemical performance test

[0141] Battery 1#

[0142] The polar group grafted aramid-based resin prepared in Example 1 was prepared into solutions, and then coated or spin-coated on the surface of sodium metal. After drying, an interface modification layer was formed on the surface of the metal electrode. A symmetrical battery was assembled using an EC / DEC electrolyte containing 1M NaPF6. The electrolyte was charged at 0.1 mA / cm 2 The polarization curves were tested under constant current with charge and discharge of 0.5h respectively, and compared with the performance of the sodium metal electrode without the interface modification layer. Figure 13-20 And as shown in Table 4.

[0143] Table 4

[0144]

[0145] Depend on Fig.13 It can be seen that in the constant current polarization of the sodium metal electrode coated with the polar group grafted aramid A interface modification layer, the battery can stably cycle 500 times.

[0146] Depend on Fig.14 It can be seen that in the constant current polarization of the sodium metal electrode coated with the polar group grafted aramid B interface modification layer, the battery can stably cycle 500 times.

[0147] Depend on Fig.15 It can be seen that in the constant current polarization of the sodium metal electrode coated with the polar group grafted aramid C interface modification layer, the battery can stably cycle 500 times.

[0148] Depend on Fig.16 It can be seen that in the constant current polarization of the sodium metal electrode coated with the polar group grafted aramid D interface modification layer, the battery can stably cycle 500 times.

[0149] Depend on Fig.17 It can be seen that in the constant current polarization of the sodium metal electrode coated with the polar group grafted aramid E interface modification layer, the battery can stably cycle 500 times.

[0150] Depend on Fig.18 It can be seen that in the constant current polarization of the sodium metal electrode coated with the polar group grafted aramid F interface modification layer, the battery can stably cycle 500 times.

[0151] Depend on Fig.19 It can be seen that in the constant current polarization of the sodium metal electrode without the interface modification layer, the battery can only cycle no more than 50 times.

[0152] Fig. 20 and 21 This is the SEM characterization of the electrode surface of the sodium metal electrode coated with the polar group grafted aramid A interface modification layer before and after 500 cycles. There is no obvious change in the electrode surface before and after the cycle, proving that the interface coated with the polar group grafted aramid resin has excellent electrochemical stability.

[0153] Fig. 22 The ATR-FTIR infrared images of polar group-grafted aramid fiber A and resin A coated on the surface of sodium metal. Among them, the characteristic peaks of the amide group of resin A are 1597 and 1644 cm -1 After coating on the sodium metal surface, the ions shifted to 1598 and 1641 cm -1 , which proves that the amide bond has a certain interaction with the sodium metal surface, and this interaction is conducive to the stable coating of aramid resin on the sodium metal surface.

[0154] Refer to Table 4 and Figure 13-22 As shown, the polar group-grafted aramid-based resin prepared in the present application has excellent electrochemical stability as a battery interface modification layer in the electrochemical cycle, and can effectively improve the cycle stability and coulombic efficiency of the sodium metal battery.

[0155] Battery 2#

[0156] The polar group grafted aramid-based resin prepared in Example 1 was prepared into solutions, and then coated or spin-coated on the surface of lithium metal. After drying, an interface modification layer was formed on the surface of the metal electrode. A symmetrical battery was assembled using EC / DEC electrolyte containing 1 M LiPF6. The polarization curve was tested. At 0.1 mA / cm 2 The polarization curve was tested under constant current with charge and discharge for 1 h respectively. The test results are shown in Table 5.

[0157] Table 5

[0158]

[0159] As shown in Table 5, it can be seen that the polar group-grafted aramid-based resin prepared in the present application can effectively improve the cycle stability and coulombic efficiency of lithium metal batteries as a battery interface modification layer.

[0160] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A polar group grafted aramid-based resin, characterized in that: The polar group-grafted aramid-based resin is an aramid polymer grafted with at least one polar group, and the structure of the polar group-grafted aramid polymer is shown in Formula 1 or Formula 2: Among them, R1 and R2 are both polar group side chains; R1 and R2 are both selected from one of ether bond groups, sulfonate groups, quaternary ammonium salt groups, carbonate groups, phosphate groups, sulfonimide groups and corresponding derivative groups.

2. The polar group grafted aramid-based resin according to claim 1, characterized in that: The structures of R1 and R2 are shown in Formula 3. *-R3-R4 formula 3; Wherein, R3 is selected from any derivative group of an aliphatic group, an aromatic group or a combination thereof; and R4 is selected from any one of an ether group, a sulfonate, a quaternary ammonium salt, a carbonate, a sulfonimide or a phosphate.

3. The polar group grafted aramid-based resin according to claim 1, characterized in that: n is selected from an integer of 10-10000; further, n is selected from an integer of 100-10000.

4. The polar group grafted aramid-based resin according to claim 2, characterized in that: The aliphatic group is a straight-chain or branched aliphatic hydrocarbon group or its fluorine-containing or silicon-containing derivative group; And / or the aromatic group is a monocyclic aromatic group, a polycyclic aromatic group or a condensed aromatic group which is unsubstituted or substituted with at least one substituent, wherein the substituent when substituted is one or more of halogen, nitro, hydroxyl or silicon-containing group.

5. The polar group grafted aramid-based resin according to claim 2, characterized in that: The ether group is an ether-containing group which is unsubstituted or substituted with at least one substituent; and / or sulfonate is a sulfate group whose counter ion is a proton or a metal ion; and / or the quaternary ammonium salt is one of the quaternary ammonium salt groups whose counter ion is a halide ion, a carboxylate, a hexafluorophosphate, a difluorooxalatoborate, a tetrafluoroborate, a trifluoromethylsulfonate, a bis(fluorosulfonylimide) or a bis(trifluoromethylsulfonylimide); and / or the carbonate is a carbonate group which is unsubstituted or substituted with at least one substituent; and / or the sulfonimide salt is a sulfonimide group whose counter ion is a proton or a metal ion; and / or phosphate is a phosphate group whose counter ion is a proton or a metal ion; Wherein, the substituent is one of halogen, nitro, hydroxyl or silicon-containing group.

6. A method for preparing a polar group grafted aramid-based resin according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1: dissolving aramid in a solution of a polar solvent and a solubilizing salt, adding a certain amount of an acid-binding agent and a halogenated polar group monomer, and stirring at a certain temperature to obtain a mixture; S2: pouring the mixture obtained in step S1 into a precipitant, and then washing, purifying and drying in sequence to obtain a polar group-grafted aramid-based resin.

7. The preparation method according to claim 6, characterized in that: In step S1, the mass fraction of the solubilizing salt is 0.1%-20%, the mass fraction of the aramid fiber is 0.1%-30%, the mass fraction of the acid binding agent is 0.1%-20%, and the mass fraction of the halogenated polar group monomer is 1%-20%.

8. The preparation method according to claim 6, characterized in that: The aramid fiber is selected from one or both of meta-aramid fiber and para-aramid fiber; and / or the polar solvent is selected from one or more of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; and / or the solubilizing salt is selected from one or more of lithium bromide, potassium bromide, zinc chloride, potassium hydroxide, sodium hydroxide, lithium chloride, calcium chloride, sodium hydride or magnesium chloride; and / or the acid-binding agent is selected from one or more of potassium hydroxide, sodium hydroxide, potassium carbonate or sodium hydride; and / or the precipitant is selected from one or more of water, methanol, ethanol, hydrochloric acid, sulfuric acid, sodium chloride and sodium carbonate solution.

9. A polar group grafted aramid resin interface modification layer, characterized in that: The polar group grafted aramid resin interface modification layer comprises the polar group grafted aramid-based resin according to any one of claims 1-5.

10. A secondary battery, characterized in that: The secondary battery comprises the polar group-grafted aramid resin interface modification layer according to claim 9.

Citation Information

Patent Citations

  • Separator for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    CN101356665A

  • A silicon-carbon anode material with an artificial SEI film, its preparation method and application

    CN113851613B

  • Sodium ion modified hard carbon material, sodium ion battery and preparation methods of sodium ion modified hard carbon material and sodium ion battery

    CN116632211A

Cited By

  • Aramid fiber coated diaphragm as well as preparation method and application thereof

    CN122436664A

  • Casting solution of sodium negative electrode anticorrosion polymer film for preparing secondary sodium sulfinyl chloride battery and application

    CN122889701A